Análise de risco e retorno do Bitcoin frente a ativos de alta volatilidade sob a perspectiva do índice de Sharpe - Andrade, Rodrigo Xavier (2022)
This study provides a comparative analysis between the Bitcoin cryptocurrency and high volatility assets of the Brazilian and American financial market from the years 2017 to 2021. For the present research, the Sharpe index was used as an indicator in order to analyze the return for each unit of currency. Assumed risk of Bitcoin and the Ibovespa, IMA-B 5+, Dow Jones Industrial Average®, S&P 500® and Nasdaq-100 indices. Two risk-free assets were used for later application in the Sharpe ratio formula, one American (DGS10) and one Brazilian (SELIC). The analysis made includes the annual returns of these mentioned assets from the period from 2017 to 2021 and also the accumulated return of the 5 years. After the analysis was done, it was found that Bitcoin in reais (BRL) had the best Sharpe ratio and also the highest annual profitability among the years and assets analyzed. If we consider the accumulated of 5 years, we find that the asset that had the best performance was Bitcoin in dollars (USD).